Sistem pengendalian intern pengeluaran kas pada Sekretariat Daerah Kabupaten Kepulauan Sangihe - Parera, Meyline Trisuksi; Kalangi, Lintje; Budiarso, Novi Swandari (Indonesia Accounting Journal, 2019)
The internal control system has an internal control structure that can control the internal control process including the control environment, accounting system, control procedures. This study aims to determine the internal control system, especially in cash disbursement activities at the Sangihe Regency Regional Secretariat which is based on the 5 (five) elements of the SPIP (government internal control system) including, control environment, risk assessment, control activities, information and communication and monitoring. The type of data used is qualitative data by conducting observations and direct interviews at the Regional Secretariat Office of the Sangihe Regency to the head of the financial subsection who knows thoroughly about cash disbursements. The results of the research obtained on the internal control system related to cash disbursements at the Regional Secretariat of the Sangihe Regency are in accordance with the 5 (five) elements of the Government Internal Control System(SPIP).